1999
DOI: 10.1021/bi990428e
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of a Methyl Group in β-Lactamase Evolution:  Free Energy Profiles and Molecular Modeling

Abstract: beta-Lactam antibiotics are generally thought to inhibit their target enzymes, the bacterial cell wall-synthesizing DD-peptidases, because of their resemblance to D-alanyl-D-alanine peptides. Although a favorable conformation of the latter does structurally resemble the beta-lactams with respect to backbone conformation, a significant difference is the presence of a D-methyl substituent on the penultimate alanine residue of the cell wall peptide. A classical beta-lactam antibiotic has a hydrogen in the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 36 publications
4
79
0
Order By: Relevance
“…This is probably because the active sites of blactamases have selected against extended sidechain D-alanyl-D-alanine peptides. 16,30 Concluding Discussion The suite of structures described here provides insight into the mode of action of a new breed of b-lactam, as well as completing the crystallographic imaging of intermediates in the R61 DDpeptidase reaction mechanism. We have shown that the similar effects of a specific peptidoglycanmimetic side-chain on the reactivity of peptide substrates and b-lactam inhibitors of the R61 DDpeptidase arise from the very similar side-chain a Least-squares fitting was performed with the program XTALVIEW using all atoms in the 16 important active site residues (S62, K65, H108, F120, T123, Y159, N161, D217, W233, Y280, R285, H298, T299, T301, S326, and N327 (146 total atoms)).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This is probably because the active sites of blactamases have selected against extended sidechain D-alanyl-D-alanine peptides. 16,30 Concluding Discussion The suite of structures described here provides insight into the mode of action of a new breed of b-lactam, as well as completing the crystallographic imaging of intermediates in the R61 DDpeptidase reaction mechanism. We have shown that the similar effects of a specific peptidoglycanmimetic side-chain on the reactivity of peptide substrates and b-lactam inhibitors of the R61 DDpeptidase arise from the very similar side-chain a Least-squares fitting was performed with the program XTALVIEW using all atoms in the 16 important active site residues (S62, K65, H108, F120, T123, Y159, N161, D217, W233, Y280, R285, H298, T299, T301, S326, and N327 (146 total atoms)).…”
Section: Resultsmentioning
confidence: 78%
“…The characteristic D-methyl group of the peptide fits into a snug hydrophobic site adjacent to the side-chain of Trp233. 8,16 If there were a corresponding 6-a-methyl group on the penicillin, it would be directed in such a way as to force the side-chain of Tyr159 out of its position in the E2 structure and thus likely impede its proposed role as a general acid/base in catalysis. 17,18 Strominger and Tipper suggested, on the basis of their structural hypothesis, that 6-a-methyl-penicillins might be better antibiotics than their unsubstituted analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, computational studies have been used extensively to study substrate binding, the role of the Zn(II) ions in catalysis, the protonation state of the active site, and inhibitor binding [37,42,[55][56][57][58][59]. All of the substrate binding models have made assumptions before the substrate was docked into the active site [37,42], and some of these assumptions have been shown to be invalid for certain substrates [43].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, computational studies have been used extensively to study substrate binding, the role of the Zn(II) ions in catalysis, the protonation state of the active site, protein dynamics, and inhibitor binding (35,(37)(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%